(3GdUMaj GdeMJQas - (3ghgfHQL, Lhfs; (3YHO GdQDha, eMeO ceGds ((3GdbGgQI (B:s (3GdOGQ GdOhdjI ddGSJKeGQGJ GdKbGajI ddfTQ hGdJhRjY,s, 1990)
(3YfOeG jYed GdUMajhf(B.s
(3JQLeI GdWHYI GdNGeSI GdEfLdjRjI(B.s
(3bGFeI HGdeUWdMGJ GdYdejI (B((3EfLdjRj(B-(3YQHj(B) : (3U(B. 697-716.s
(3gGOj(B.s
1 6.
Keywords: (3GdUMGaI (B((3egfI(B)s